(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The purpose of study was to study the features of extracranial cerebral hemodynamics in acute ischemic disorders of cerebral circulation - cardioembolic, atherosclerotic and lacunar infarctions in rheumatological patients. We examined 100 patients with ischemic strokes of hemispheric localization, of which 25 (25%) had cardioembolic stroke, 25 (25%) had stroke of atherosclerotic origin, and 50 (50%) had lacunar stroke who treated in in department of rheumatology of Tashkent medical academy. 20 examined people made up the control group. The main neurological manifestations of hemispheric ischemic stroke were characterized by the predominance of focal symptoms: central paresis of the 7th and 12th nerves, the presence of mono-, hemiparesis or hemiplegia, the appearance of pathological reflexes, reflexes of oral automatism, combined with sensory disorders in the form of superficial or total mono and hemianesthesia. In patients with lacunar stroke, signs of diffuse vasospasm of the BCS predominated (85%), with a predominance on the side of the affected hemisphere with an increase in the level of LSC and IMT, as well as the level of peripheral resistance and vascular tone. The results of the studies indicate that strokes of cardioembolic stroke and atherosclerotic origin develop as a result of arterio-arterial thromboembolism, and in lacunar stroke the hemodynamic mechanism of stroke development prevails.